EFEKTIFITAS PENGGUNAAN MEDIA PEMBELAJARAN FILM ANIMASI NUSSA DAN RARA DALAM MENINGKATKAN PEMAHAMAN NILAI-NILAI KARAKTER SISWA KELAS 2 DI SDN 42 AMPENAN - Baiq Eka Prihartini; H. Muhammad Makki; Muhammad Erfan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine the effectiveness of using the Nussa and Rara animated film learning media in increasing the understanding of the character values ​​of grade 2 students at SDN 42 Ampenan. This type of research is experimental research using a Pre-experimental design of the One Group Pretest-Posttest type. The research instruments used were observation and written tests in the form of multiple choices. Before conducting an assessment of the hypothesis, a prerequisite test is carried out, namely the normality test. The normality test results obtained a significance value for the pretest data of 0.098>0.05 and a posttest significance value of 0.099>0.05, which means that the data is normally distributed. After the data is normally distributed, a hypothesis test is carried out using a paired simple t-test with a value of 0.000<0.05. This means that HO is rejected and Ha is accepted, which means there is a significant difference in the means. Based on the results of the N-Gain Score test calculation, it shows that the average N-Gain score for the experimental class is 0.7274 or 72%, including the effective category, which means it can be concluded that the use of learning media for the animated film Nussa and Rara is effectively used in increasing understanding of values. character of grade 2 students at SDN 42 Ampenan.